Provider-initiated HIV testing in health care settings: Should it include client-centered counselling? - Susan M Kiene; Michael Stein; Moses Bateganya; Rhoda Wanyenze; Kenneth Mayer; Haruna Lule (Taylor & Francis Group, 2009)
To increase access to HIV testing, the WHO and CDC have recommended implementing provider-initiated HIV testing (PITC). To address the resource limitations of the PITC setting, WHO and CDC suggest that patient-provider interactions during PITC may need to focus on providing information and referrals, instead of engaging patients in client-centered counselling, as is recommended during client-initiated HIV testing. Providing HIV prevention information has been shown to be less effective than client-centered counselling in reducing HIV-risk behaviour and STI incidence. Therefore, concerns exist about the efficacy of PITC as an HIV prevention approach. However, reductions in HIV incidence may be greater if more people know their HIV status through expanded availability of PITC, even if PITC is a less effective prevention intervention than is client-initiated HIV testing for individual patients. In the absence of an answer to this public health question, adaptation of effective brief client-centered counselling approaches to PITC should be explored along with research assessing the efficacy of PITC.